2022
DOI: 10.3389/fendo.2022.896507
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Ubiquitin Ligase RNF149 in the Development of Rat Neonatal Gonocytes

Abstract: Male reproductive function depends on the formation of spermatogonial stem cells from their neonatal precursors, the gonocytes. Previously, we identified several UPS enzymes dynamically altered during gonocyte differentiation. The present work focuses on understanding the role of the RING finger protein 149 (RNF149), an E3 ligase that we found to be strongly expressed in gonocytes and downregulated in spermatogonia. The quantification of RNF149 mRNA from postnatal day (PND) 2 to 35 (puberty) in rat testis, bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…1 ). To date RNF149 was reported to be involved in gonocyte development and BRAF induced proliferation 32 , 33 . Our data presented herein reveal a new role for RNF149 in pEQC processes.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). To date RNF149 was reported to be involved in gonocyte development and BRAF induced proliferation 32 , 33 . Our data presented herein reveal a new role for RNF149 in pEQC processes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that RNF149 promotes cell survival in colorectal cancer [10] and inhibits cell migration in NPC [11]. Additionally, RNF149 is found to involve the development of rat neonatal gonocytes [29]. Recently, a study showed that RNF149 interacts with components of pre-emptive ER associated quality control (pEQC) pathway, regulating the translocation of misfolded proteins [30].…”
Section: Discussionmentioning
confidence: 99%